Nutrient cycling characteristics along a chronosequence of forest primary succession in the Hailuogou Glacier retreat area, eastern Tibetan Plateau - Yang, Danli; Luo, Ji; Shu, Shumiao; Hu, Yan; Tang, Hongsong; Li, Xuemei (PeerJ (San Francisco, CA), 2025)
The Hailuogou Glacier has been continuously retreating since the end of the Little Ice Age, resulting in a 125-year soil chronosequence and a complete primary forest succession sequence. Nutrient cycling and utilization are the foundation to forest succession processes and dynamic changes, directly influencing the structure and stability of ecosystems. However, our understandings on the characteristics of ecosystem nutrient accumulation and recycling during succession, especially in the context of primary succession within glacier retreat areas, remain limited. To address this, we investigated nutrient characteristics across six forest primary succession sites in the Hailuogou Glacier retreat area. Six sites representing three forest stages: the pioneer plant stage (S1), the broad-leaved forest stage (S2-S4), and the coniferous forest stage (S5-S6). Three quadrats were established at each site, and measurements of biomass as well as soil characteristics were documented within each quadrat. Subsequently, we collected samples of vegetation, soil and litter. By measuring the concentrations of N, P, K, Ca, and Mg in vegetation and soil and combining with the data of the quadrat survey, the pools and nutrient characteristics of N, P, K, Ca, and Mg in various components of the ecosystem were calculated at each site. Our findings indicated that: (1) Nutrient pools, excluding the soil C layer, increased with forest primary succession, reaching 5,995.71 kg hm N, 461.83 kg hm P, 3,798.09 kg hm K, 7,559.81 kg hm Ca and 1,948.13 kg hm Mg at site S6; however, the pools of P, K, and Mg in the Oa layer, and Ca and Mg in the tree layer, attained their peak levels at sites S3 to S4. (2) The pools of N, Ca, and Mg in the organic soil were significantly greater than vegetation. Although over 60% of the P and K were stored in the organic soil at site S1, these proportions shifted, with vegetation holding 60.71% of P and 56.86% of K at site S5. (3) Broad-leaved forests exhibited higher nutrient return, cycling, and absorption, thereby accelerating nutrient circulation and depleting soil nutrients to maintain growth. In contrast, coniferous forests were more efficient at nutrient utilization and storage, retaining nutrients and maintaining high biomass and productivity in nutrient-poor environments. Overall, these findings highlighted that the nutrients in each component of the ecosystem continue to accumulate with forest primary succession. Coniferous forests' nutrient cycling mechanisms offer a competitive edge in nutrient-poor environments, enhancing ecosystem stability.